2022
DOI: 10.3390/medicina58070950
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia and Heart Rate Fluctuation Are Associated with a Prolonged Intensive Care Unit Stay in Patients with Severe COVID-19

Abstract: Background and Objective: Bradycardia has been observed among patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is suspected to be associated with poorer outcomes. Heart rate (HR) fluctuation has been found to be correlated with a greater mortality rate in critically ill patients. The association of bradycardia and HR fluctuation with the outcome of severe coronavirus disease 2019 (COVID-19) patients has not been clarified. Therefore, we aimed to examine whether bradycardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Critical illness with SARS-CoV-2 is associated with poor outcomes and a high mortality rate because critical illness disturbs multiple organ systems including the heart function which makes patients on remdesivir therapy more vulnerable to bradycardia ( Dessie and Zewotir, 2021 ; Gao et al, 2021 ). A study by Tajarernmuang et al ( Tajarernmuang et al, 2022 ) evaluated bradycardia and heart rate fluctuation in critically ill COVID-19 patients, and they found 71.1% (62/86) of the patient had bradycardia and those patients had longer intensive care unit length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness with SARS-CoV-2 is associated with poor outcomes and a high mortality rate because critical illness disturbs multiple organ systems including the heart function which makes patients on remdesivir therapy more vulnerable to bradycardia ( Dessie and Zewotir, 2021 ; Gao et al, 2021 ). A study by Tajarernmuang et al ( Tajarernmuang et al, 2022 ) evaluated bradycardia and heart rate fluctuation in critically ill COVID-19 patients, and they found 71.1% (62/86) of the patient had bradycardia and those patients had longer intensive care unit length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have also shown a correlation between rapid pulse (arrhythmia) and increased mortality. [36][37][38][39][40][41] Zhang et al found that a rapid resting pulse rate increases the risk of all-cause mortality by 6% and cardiovascular mortality by 8%. This increase in mortality is believed to be caused by an imbalance between the vagus nerve, the sympathetic nervous system, and the autonomic nervous system, which leads to a rapid pulse.…”
Section: Vital Signsmentioning
confidence: 99%